Building brand awareness and engagement with video content on Facebook - Samattapan, Kittikarn; Tadaamnuaychai, Montira (Siam Communication Review, 2025)
Two research objectives are pursued in this study on "Building brand awareness and engagement with video content on Facebook pages": 1) Research how to use short videos to communicate on Facebook in order to increase brand awareness for the balloon art company; 2) Create content for the balloon art company’s Artinflate Facebook page that shows behind-the-scenes work; and 3) Determine which real-time and behind-the-scenes videos produce the best results by tracking the results on the balloon art company’s Facebook page. The study employs the Experimental Research Method and measures the effectiveness of the video content campaign behind the scenes of Balloon Art Company before it begins. This is done by using Engaged and the number of followers on the Facebook page as indicators of the campaign’s success in increasing brand recognition and awareness as well as viewer engagement on the Facebook platform. The data collection process is divided into two phases: Stage 1 involves posting behind-the-scenes video content ads and gathering data for two months. Stage 2 involves posting two different kinds of video content ads—behind-the-scenes and real-time—and comparing them. The data collection period was one month. According to the study’s findings, employing video content that is relevant to the event’s theme can boost target audience engagement with the business, particularly when it comes to social media viral content. With 14,859 persons reached and 25,304 impressions, the "Whale" campaign got the highest reach and impressions. To leverage the research findings for future content development, the company should start filming behind-the-scenes footage of the entire production process, from the day of the event until it is installed in the actual location. Other platforms should be investigated as well in order to satisfy a wider variety of target audiences.